PENGARUH MOTIVASI, KOMPETENSI DAN KEPUASAN KERJA TERHADAP KINERJA KEPALA SEKOLAH - Supono, Boedyo - (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2006)
ABSTRACT The research is a survey research administered on junior high school headmasters in Education, Youth and Sports Bureau of Surakarta Municipality. Data required in the research are respondent’s perception on motivation, competence, work satisfaction, and headmaster’ performance. The data resources are primary and secondary data. The data collection method is using questionnaire technique. The sampling method is done using systematic sampling method. The result of the research concludes that: 1) there is a significant effect of motivation on headmaster’s performance. It is proved with the t statistics of 2,946 and p < 0,05; 2) there is a significant effect of competence on headmaster’s performance. It is proved with the t statistics of 17,089 and p < 0,05; 3) there is a significant effect of work satisfaction on headmaster’s performance. It is proved with the t statistics of 2,296 and p < 0,05.; and 4) there is a significant effect of motivation, competence and work satisfaction on headmaster’s performance simultaneously. It is proved with the F statistics of 844,238 and p < 0,05. The determination coefficient (R2) is 0,973 means that the variability of 97,3% of headmasters’ performance in Surakarta is determined by motivation, competence, and work satisfaction, whereas the remaining of 2.7% is determined by other factors beyond the model. Therefore, it is suggested to the related institution to pay its attention and improve factors affecting headmasters’ performance in its efforts to actualize lifelong education. Keywords: motivation, competence, work satisfaction